Determinantes de la eficiencia en las cooperativas del segmento 3 del sector financiero del Ecuador en los periodos 2019-2022 - Sabando Bravo, Daniela Nicolle (2024)
This research project focuses on analyzing the determinants of efficiency in cooperatives in segment 3 of the financial sector in Ecuador during the periods 2019-2022. Bibliographic research was carried out and the savings and credit cooperatives in segment 3 were considered as the population, obtaining a sample of 39 cooperatives. This study has a mixed approach, using analytical and descriptive methods, as well as various research techniques, such as bibliographic review, financial analysis and financial indicators, and characterization sheets. The initial phase consisted of studying these cooperatives to analyze their current situation. The CAMEL method was also used to evaluate aspects such as portfolio, assets and administrative efficiency. The majority of these cooperatives offer basic services such as savings accounts and consumer loans; there is notable variability in the breadth and diversity of the services offered. Some, such as vehicle or educational loans, are scarce in several cooperatives, which shows the need to improve the dissemination and clarity of information. In relation to financial performance, the savings and credit cooperatives in segment 3 show variability in their Return on Assets (ROA) throughout the years analyzed, although notable improvements are observed in 2022. Some progress in administrative efficiency stands out, indicating more effective management of resources. However, challenges remain, pointing to the need for strategic measures to improve this aspect and ensure the sustainability of these institutions.